Investigation of intestine function during acute viral hepatitis using combined sugar oral loads. Issue 11 (November 1987) - Parrilli, G; Cuomo, R; Nardone, G; Maio, G; Izzo, C M; Budillon, G
Abstract : One fifth of all cases of A virus hepatitis (AVH) have symptoms of gastroenteritis at the onset. This study investigated the mediated intestinal absorption of D-xylose (D-xyl) and 3-o-methyl-D-glucose (3-omG) and the non-mediated permeation of lactulose (Lacl, mol wt 342) and L-rhamnose (L-rh, mol wt 164) during acute and remission phases of AVH. Ten patients with AVH were given an oral load containing these sugars (5 g D-xyl: 2.5 g 3-omG, 1 g L-rh, 5 g lacl in 250 ml water) once during the acute phase and again during remission. The same load was given once to a group of 22 healthy controls. The mean concentration of D-xyl in urine and the ratio of D-xyl to 3-omG in plasma and urine were normal in both the AVH phases, ruling out intestinal malabsorption even in the acute phase. This study showed a significant increase in non-mediated permeation to Lacl, but not to L-rh, during the acute phase. These data indicate that the barrier function of the intestine is compromised in AVH infection while the absorptive function is not. An abnormally low concentration of D-xyl and 3-omG in plasma at one hour was found in all patients during the acute phase. This finding cannot be explained by alterations in intestinal absorption, but could be accounted for by increased space distribution of the sugars because of increased diffusion into tissue cells and/or expansion of the extracellular space by fluid retention.